Eksistensi Wakaf Uang di Indonesia Sebagai Jembatan Kesejahteraan : Potensi dan realisasi wakaf uang di Indonesia - Nur Fadlilah, Khafidha; Helena Angel Likha; Yuniar Tri Wulandari; Rinda Asytuti (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This research aims to provide an in-depth understanding of the existence and role of cash waqf in Indonesia as a bridge to community welfare. The method used in this research is a descriptive qualitative or data-based research, data collection techniques are carried out by looking for data sources such as journals, opinions, news articles, and waqf tables in Indonesia from the Indonesian Waqf Institution. The results of this research are that cash waqf is a solution to the problem of social inequality, and can have the potential for community welfare. Cash waqf opens space for someone who wants to give waqf without waiting to become a landlord. This research implies that the existence of cash waqf is a bridge to community welfare because of the benefits that can be felt by the public.